(untitled) (Proceedings OPTIMAL, 2025)
Abstract Gout (Gout Arthritis) is caused by a buildup of uric acid in the body’s joints. When there is excessuric acid in the bloodstream and more than can be excreted, the uric acid seeps into the joint tissue, causing pain and swelling. The aim of this research is to analyze the effectiveness ofgiving compresses with grated red ginger to treat joint pain in elderly patients with gout. The research design used a one group pre test–post test, with the aim of determining the effectof compresses with grated red ginger to treat joint pain in elderly patients with gout. The datacollection instrument uses observation sheets for the pretest and posttest. The number of respondents in this study was 16 respondents. Elderly people who did ginger compress therapy experienced a decrease in pain, the number of pain reduction before treatment was carried out,there were 8 respondents with mild pain, and after treatment there were 2 people. There were 8 respondents with moderate pain before treatment, 3 respondents after treatment, and 11 respondents who felt moderate pain after treatment. Based on the results of statistical tests using the paired sample t test or paired test, the p-value = 0.014, because the p-value <0.05,there is a decreasing relationship before and after giving compresses with grated red ginger to treat joint pain. in elderly patients with gout in the Siulak Gedang Community Health Centerworking area in 2024. It is recommended for gout sufferers to compress ginger solution at home using simple tools that are affordable to all levels of society, and this action is an alternative way to reduce pain.